Preservation of ∼12-h ultradian rhythms of gene expression of mRNA and protein metabolism in the absence of canonical circadian clock - Zhu, Bokai; Liu, Silvia (Frontiers in Physiology, 2023)
Besides the ~24-hour circadian rhythms, ~12-hour ultradian rhythms of gene expression, metabolism and behaviors exist in animals ranging from crustaceans to mammals. Three major hypotheses were proposed on the origin and mechanisms of regulation of ~12-hour rhythms, namely that they are not cell-autonomous and controlled by a combination of the circadian clock and environmental cues, that they are regulated by two anti-phase circadian transcriptional factors in a cell-autonomous manner, or that they are established by a cell-autonomous ~12-hour oscillator. To distinguish among these possibilities, we performed a post-hoc analysis of two high temporal resolution transcriptome dataset in animals and cells lacking the canonical circadian clock. In both the liver of BMAL1 knockout mice and Drosophila S2 cells, we observed robust and prevalent ~12-hour rhythms of gene expression enriched in fundamental processes of mRNA and protein metabolism that show large convergence with those identified in wild-type mice liver. Bioinformatics analysis further predicted ELF1 and ATF6B as putative transcription factors regulating the ~12-hour rhythms of gene expression independently of the circadian clock in both fly and mice. These findings provide additional evidence to support the existence of an evolutionarily conserved 12-hour oscillator that controls ~12-hour rhythms of gene expression of protein and mRNA metabolism in multiple species.